(untitled) (Bangladesh Medical Journal, 2014)
Urinary stone disease is a major problem due to its high prevalence and incidence and recurrence. The present study aimed to determine the outcome of in situ Extracorporeal Shock-Wave Lithotripsy (ESWL) for mid-ureteric stone in terms of stone clearance, per operative and post operative complications involving 30 patients with mid ureteric stone with less than 10 mm in diameter in the Department of Urology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka between September 2011 and August 2012. Seventeen (56.7%) patients had stone in the right ureter and 13(43.3%) had stone in the left ureter. Mean of stone size was 8.07 mm with a range of 6-10 mm. Most of the patients (96.7%) had post procedure pain, 15(50.0%) had haematuria and 9(30.0%) had fever. Final outcome of treatment showed that complete stone clearance was seen in 83.3% patients after one month. Mid ureteric stone clearance with ESWL was more than eighty percent with a very low rate of complications. ESWL may be recommended as safe and first line therapy for mid ureteric stones. DOI: http://dx.doi.org/10.3329/bmj.v43i2.21386 Bangladesh Med J. 2014 May; 43 (2): 72-78